ANALISIS KEMAMPUAN LABA USAHA PEMBIBITAN KELAPA SAWIT PADA PT. DIAN ABDI NUSA DI KABUPATEN KUTAI BARAT - ., Saparudin (EKONOMIA, 2013)
SAPARUDIN. Faculty Of Economics University 17 August 1945 Samarinda, Analysis Ability Of Income From Operation Seed Coconut of Sawit [At] PT. Oil Lamp Serve Nusa [In] Sub-Province of Kutai West, Under tuition Mr. Prof. Dr. LCA. Robin of Jonathan, MM., M.Si And Father of Heriyanto, SE., MM Intention of this writing is to analyse acquirement of income from operation [at] Coconut seed of Sawit [in] PT. Oil Lamp Serve Nusa [In] Sub-Province of Kutai West year 2010, 2011 and 2012. In line with this writing, hence told solution fundamental " Is perolehasn of coconut seed income from operation of Sawit [at] PT. Oil Lamp Serve Nusa [In] Sub-Province of Kutai West in the year 2010, 2011 and 2012 experiencing of improvement.Pursuant to problems of fundamental, hence raised [by] the following hypothesis : " Ability of profit [at] coconut seed of sawit PT. Oil lamp Serve Nusa [in] Sub-Province of Kutai West in the year 2010, 2011 and 2012 experiencing of improvement". Analyzer which [is] used in this research [is] Ratio ability of profit ( Profitabilitas) with dot weigh against [at] growth of ability of profit of year 2010, 2011 up to 2012.After passing research phase, solution and analysis known that Profitability Company Seen from Net Profit Margin of year 2010 to 2011 increase equal to 7%, while from year 2011 to 2012 experiencing of increase equal to 17%. Becoming conclusion of natural Net Profit Margin [of] improvement or have is effective. Seen from Return On Inverstmen 2010 to 2011 experiencing of increase equal to 33%, while from year 2011 to 2012 experiencing of increase equal to 37%. Becoming conclusion of natural Return On Inverstmen [of] improvement or have is effective. Seen from Return On Equity in the year 2010 equal to 30 , in the year 2011 equal to 38% and in the year 2012 equal to HALTED. CROSSING PARAGRAPH LIMITATION%.